2013
DOI: 10.4103/0970-1591.109977
|View full text |Cite
|
Sign up to set email alerts
|

An audit of suprapubic catheter insertion performed by a urological nurse specialist

Abstract: Aims:To introduce the concept that a urological Nurse Specialist can perform Suprapubic Catheter (SPC) insertions independently without significant complications, if systematic training is given.Settings and Design:Retrospective study.Materials and Methods:A retrospective audit of Suprapubic Catheter insertions performed by a Urological Nurse Specialist was conducted between April 2009 and April 2011.Results:Of the total 53 patients, in 49 (92.45%) the procedure was successful. Out of the remaining four, two (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…[1], who reported a rate of 2.4% in 2006. More recent studies demonstrate a significantly lower risk of bowel injury of <1% [4–12] but it is difficult to make direct comparisons between these studies due to differences in study design and populations [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1], who reported a rate of 2.4% in 2006. More recent studies demonstrate a significantly lower risk of bowel injury of <1% [4–12] but it is difficult to make direct comparisons between these studies due to differences in study design and populations [13].…”
Section: Discussionmentioning
confidence: 99%
“…Zacharia et al. [10] described a surgical exploration for a misplaced catheter which had traversed the peritoneum but had not injured the bowel. Hall et al.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the rates of bowel injury prior to the NPSA alert and the publication of the original BAUS guidelines suggests a historical bowel injury risk of approximately 2.5% [4,5]. Studies published subsequent to the NPSA alert and BAUS guideline publication suggest a bowel injury rate of 0–0.2% [7–12,28]. Caution must be exercised when drawing conclusions from the comparison of these different studies, as differences in populations and methodology will introduce bias.…”
Section: Complicationsmentioning
confidence: 99%
“…Shortly afterwards, the BAUS published guidelines for safe SPC insertion [6]. Subsequent studies have reported a lower rate of bowel injury of 0–0.2% [7–12], suggesting a significant impact from the original BAUS guideline. We present an update to the BAUS guideline in light of these new data.…”
Section: Introductionmentioning
confidence: 99%
“…Since the NPSA reports more recent studies have reported much lower rates of BI from 0% to 0.2%, based on datasets ranging from 24 to 585 SPC insertions between 2011 to 2014. [8][9][10][11][12][13] Metanalysis of these data shows a BI rate of 1/1086, 0.09%.…”
Section: Meta-analysismentioning
confidence: 99%